Modeling and simulation of solid oxide fuel cell based on the volume–resistance characteristic modeling technique - Wang, Lijin; Zhang, Huisheng; Weng, Shilie (Journal of power sources, 2008)
Solid oxide fuel cell (SOFC) is a complicated system with heat and mass transfer as well as electrochemical reactions. The real-time dynamic simulation of SOFC is still a challenge up to now. This paper develops a one-dimensional mathematical model for direct internal reforming solid oxide fuel cell (DIR-SOFC). The volume–resistance ( V– R) characteristic modeling technique is introduced into the modeling of the SOFC system. Based on the V– R modeling technique and the modular modeling idea, ordinary differential equations meeting the quick simulation are obtained from partial differential equations. This model takes into account the variation of local gas properties. It can not only reflect the distributed parameter characteristics of SOFC, but also meet the requirement of the real-time dynamic simulation. The results indicate that the V– R characteristic modeling technique is valuable and viable in the SOFC system, and the model can be used in the quick dynamic and real-time simulation.